Polarographic Studies of Lisinopril - Rajasekaran, A.; Murugesan, S. (Asian Journal of Chemistry, 2010)
A novel and simple polarographic method is described for the estimation of lisinpril and its pharmaceutical formulation. The polarogram was recorded from +200 mV to -1.0 V using 0.5 M acetic acid and 10 mM copper sulphate as background electrolyte and calomel electrode as reference electrode.